Print Grades Prime: A quantitative analysis of producer communication preferences of U.S. beef breed association magazines through the lenses of uses, gratifications, and gatekeeping - Megan Underwood; Katherine J. Starzec; Nellie Hill-Sullins; R. L. Weaber (Journal of Applied Communications, 2024)
The United States beef industry is a major stakeholder in national and international agriculture and is driven by technological innovations and beef producers in all 50 states. Beef cattle breed associations are essential to the success of the industry as they not only maintain breed pedigrees but also disseminate vital information to their members. The magazines of beef cattle breed associations are a primary source of communication for U.S. beef producers. Goals for this study were to determine what information beef producers use from their beef breed association magazines, what information they want to see more of in beef breed association magazines, and if producers prefer the magazines in a print or digital format. Uses and gratifications theory, which focuses on the reasons why individuals choose to use a specific communication medium; the effect the medium has on the individual; and the gratifications received through its use, guided this study, along with gatekeeping theory. We used a descriptive quantitative survey research design to disseminate a survey instrument to members of six U.S. beef breed associations. Results revealed a large percentage of survey respondents prefer their beef breed association magazines in a print format. Additionally, results indicate that respondents use association magazines for a variety of information, and they want to see more information related to breed improvement strategies, genetic selection, and technological advancements. Results revealed insightful uses of magazine topics related to breed associations and can be used as a resource to help guide the editorial content of the magazines. We recommend beef cattle breed associations continue to provide magazine content in both print and digital formats and include editorial topics curated to the needs of the beef producers using their magazines.
Keywords: Beef cattle breed associations; print magazines; uses and gratifications; communications; beef producers; survey research; gatekeeping